PERENCANAAN PEMBANGUNAN SEKTOR PARIWISATA DI KABUPATEN MINAHASA TENGGARA - Kawengian, Filly; LENGKONG, FLORENCE DAICY; POMBENGI, JERICHO DANGA (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstrack : To achieve a development plan, especially in the field of tourism is to provide comfort for visitorsand positive impact in the field of social and cultural and ensure the effective use of resources that affectthe field of globalization. But nevertheless see the development that has been compiled then need a goodplanning to achieve the purpose of development.In this study using qualitative research methods are descriptive. Informan research is head ofDepartemen Tourism and Culture of South-eastern Minahasa Regency, secretary of service, staff, head ofsub planning section, Visitors and the public; the total of number informants is 7 people. Data collection isby interview, observation and documentation techniques. On data analysis using descriptive qualitative datatechnique from Sugiono.Based on the results of research undertaken it can be concluded that still need to be in developmentplanning in nature tourism Aer Konde in village Wawali, Ratahan Districts. Because there is, still a lack offacilities to support the attractiveness of tourists who come in nature tour Aer Konde, for that existence ofdevelopment planning from each party related in development of existing tourism in Southern MinahasaRegency.From the results of these studies it can be suggested suggestion that is: (1) From related parties inthis development can better organize the development through environmental factors by ensuringcleanliness, in order to attract the attention of every tourist who come to visit. (2) It is expected that there iscooperation from the government, related communities and visitors in the tourist Aer Konde. (3)Stakeholders in development planning is expected so that the planning process can run well. (4) The needfor more extensive information, so that more visitors who come in tourist Aer Konde. (5) and more fundsare needed to support existing development plans at tourism sites in Southern Minahasa Regency.Keywords: Development, Planning, Tourism Sector.